(untitled) (World Economics and Finance Bulletin, 2026)
In the context of the global transition toward a knowledge-based economy, the development of talent in higher education has become a strategic priority. This article examines measures to strengthen the institutional framework of centers for nurturing gifted students at higher education institutions. The study analyzes key organizational, financial, and managerial challenges affecting the effectiveness of these centers, including insufficient integration into university governance, limited funding sources, and weak external collaboration. Based on a comprehensive analysis, the research proposes practical recommendations aimed at improving institutional capacity, enhancing human resource potential, and fostering innovation-oriented environments. The findings highlight the importance of adopting integrated management approaches, expanding partnerships with industry and international organizations, and implementing performance evaluation systems to ensure sustainable development.